„Stworzył mężczyznę i niewiastę” (Rdz 1,27). Antropologia pisarzy wczesnochrześcijańskich (Sekcja Patrystyczna, Kamień Śląski, 23‑25.09.2024) - Ludewicz, Michal Jan (Vox Patrum, 2024)
The text contains a report from the meeting of the Polish Patristic Section, which took place on September 23-25, 2024 in Kamień Śląski.